Adverse events associated with pediatric exposures to dextromethorphan. (2nd January 2017) - Paul, Ian M.; Reynolds, Kate M.; Kauffman, Ralph E.; Banner, William; Bond, G. Randall; Palmer, Robert B.; Burnham, Randy I.; Green, Jody L.
Abstract: Study objective: Dextromethorphan is the most common over-the-counter (OTC) antitussive medication. We sought to characterize adverse events associated with dextromethorphan in children <12 years old from a surveillance program of OTC cough/cold medication exposures. Methods: This is a retrospective case series of oral exposures to dextromethorphan with ≥1 adverse event from multiple U.S. sources (National Poison Data System, FDA Adverse Event Reporting System, manufacturer safety reports, news/media, medical literature) reported between 2008 and 2014. An expert panel determined the relationship between exposure and adverse events, estimated dose ingested, intent of exposure, and identified contributing factors to exposure. Results: 1716 cases contained ≥1 adverse event deemed at least potentially related to dextromethorphan; 1417 were single product exposures. 773/1417 (55%) involved only one single-ingredient dextromethorphan product (dextromethorphan-only). Among dextromethorphan-only cases, 3% followed ingestion of a therapeutic dose; 78% followed an overdose. 69% involved unsupervised self-administration and 60% occurred in children <4 years old. No deaths or pathologic dysrhythmias occurred. Central nervous system [e.g., ataxia ( N  = 420)] and autonomic symptoms [e.g., tachycardia ( N  = 224)] were the most common adverse events. Flushing and/or urticarial rash occurred in 18.1% of patients. Dystonia occurred in 5.4%. Conclusions: No fatalities were identified in this multifaceted surveillance program following a dextromethorphan-only ingestion. Adverse events were predominantly associated with overdose, most commonly affecting the central nervous and autonomic systems.